2021
DOI: 10.1093/molbev/msab114
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis Suggests Evolution of Ribosome Specificity in Modern Elongation Factor-Tus from “Generalist” Ancestors

Abstract: It has been hypothesized that early enzymes are more promiscuous than their extant orthologues. Whether or not this hypothesis applies to the translation machinery, the oldest molecular machine of life, is not known. Efficient protein synthesis relies on a cascade of specific interactions between the ribosome and the translation factors. Here, using Elongation factor-Tu (EF-Tu) as a model system, we have explored the evolution of ribosome specificity in translation factors. Employing pre-steady state fast kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Other distantly related nitrogenase-like homologs have putative catalytic roles, including a recently reported homolog suggested to participate in a methionine salvage pathway that forms ethylene (North et al 2020). It is possible that a maturase-like predecessor would have been promiscuous, a suggested general feature of early-evolved proteins (Copley 2015; De Tarafder et al 2021), and capable of both providing a scaffold for cluster maturation as well as catalysis using the same matured cluster. Gene duplication and divergence might then have subsequently specialized maturases to only function as a scaffold and evolve residues that permit the release of the matured cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Other distantly related nitrogenase-like homologs have putative catalytic roles, including a recently reported homolog suggested to participate in a methionine salvage pathway that forms ethylene (North et al 2020). It is possible that a maturase-like predecessor would have been promiscuous, a suggested general feature of early-evolved proteins (Copley 2015; De Tarafder et al 2021), and capable of both providing a scaffold for cluster maturation as well as catalysis using the same matured cluster. Gene duplication and divergence might then have subsequently specialized maturases to only function as a scaffold and evolve residues that permit the release of the matured cluster.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the ribosome and its protein factors were already established in LUCA 4,6 . Expansion of the translation machinery, on the other hand, is thought to have occurred prior to LUCA 68 potentially following the rRNA core center of the ribosome formation, 31,69 strengthening the hypothesis that, unlike the ribosome, 70 the supporting translational factors were not yet fully established in the early cellular era. While we do not know if LUCA had adapted a system that is largely similar to the extant translation machinery, or whether translation‐as‐we‐know‐it subsequently emerged in a stepwise fashion or through simultaneous maturation of supporting components, 71,72 tracing the evolutionary history of early translation factors will unravel the fascinating story of life's core information processing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The other copy, the EF‐Tu ancestor, coevolved with tRNAs, gaining flexible conformational function in the GTP‐binding domain, and acquired mutations to bind a wider variety of tRNA molecules, specializing for EF‐Tu functionality. Intriguingly, it was recently shown that ancestral EF‐Tu proteins were generalists in terms of their compatibility with ribosomes, compared to the modern EF‐Tus 31 . The translation system consists of numerous essential molecules and the complete picture of evolutionary trajectory of translation over geologic time will require an integrated view into other components such as the other translation GTPases (e.g., EF‐G, RF3) and tRNAs 67 with the underlying chemical systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations